MS/MS analysis of four scorpion venoms from Colombia: a descriptive approach (2021)
Background: Scorpions are widely known for the neurotoxic effects of their venoms, which contain peptides affecting ionic channels. Although Colombia is recognized for its scorpion diversity, only a few studies are available describing the venom content. Methods: In this descriptive study, we analyzed the MS/MS sequence, electrophoretic and chromatographic profile linked to a bioinformatics analysis of the scorpions Chactas reticulatus (Chactidae), Opisthacanthus elatus (Hormuridae), Centruroides edwardsii (Buthidae) and Tityus asthenes (Buthidae) from Colombia. Results: Each scorpion showed a specific electrophoretic and chromatographic profile. The electrophoretic profiles indicate the presence of high molecular mass compounds in all venoms, with a predominance of low molecular mass compounds in the Buthidae species. Chromatographic profiles showed a similar pattern as the electrophoretic profiles. From the MS/MS analysis of the chromatographic collected fractions, we obtained internal peptide sequences corresponding to proteins reported in scorpions from the respective family of the analyzed samples. Some of these proteins correspond to neurotoxins affecting ionic channels, antimicrobial peptides and metalloproteinaselike fragments. In the venom of Tityus asthenes, the MSn analysis allowed the detection of two toxins affecting sodium channels covering 50% and 84% of the sequence respectively, showing 100% sequence similarity. Two sequences from Tityus asthenes showed sequence similarity with a phospholipase from Opisthacanthus cayaporum indicating the presence of this type of toxin in this species for the first time. One sequence matching a hypothetical secreted protein from Hottentotta judaicus was found in three of the studied venoms. We found that this protein is common in the Buthidae family whereas it has been reported in other families – such as Scorpionidae – and may be part of the evolutionary puzzle of venoms in these arachnids. Conclusion: Buthidae venoms from Colombia can be considered an important source of peptides similar to toxins affecting ionic channels. An interesting predicted antimicrobial peptide was detected in three of the analyzed venoms.